Human perspectives on critical success factors for project risk management systems : A case study in a multinational construction company - Perttilä, Rikhard (My University, 2025)
The construction industry is characterized by high levels of risk as construction projects, which lie at the core of business operations in the industry, are typically complex, involve multiple stakeholders, and are often executed under uncertain and dynamic conditions. Therefore, effective project risk management (PRM) is crucial for long-term success. However, implementing PRM systematically remains challenging, especially in multinational organizations where human, cultural, and contextual variables add further complexity. This thesis explores how multinational construction companies can enhance their project risk management capabilities by addressing three research sub-questions: “What are the key components of an effective project risk management system (PRMS)?”, “What are the main barriers for utilizing PRMS effectively in multinational construction organizations?” and “What critical success factors (CSFs) enable the effective implementation and development of PRMS in multinational construction organizations?”. By answering these questions, the research aimed to provide both academic and practical insights to guide PRMS development. The study adopts qualitative single-case research approach, combining theoretical insights with empirical data gathered through semi-structured interviews with subject matter experts. While prior research has often focused on tools, processes, or frameworks, this thesis highlights how PRMS effectiveness is shaped by interdependent and multilayered human, cultural and contextual factors, such as leadership behaviour, trust, communication, and shared responsibility alongside structural and procedural elements. This allowed for a deeper understanding of how these dimensions interact in practice and supported the integration of theory with empirical insights. Key findings emphasize that PRMS implementation is not a purely technical exercise, but a dynamic process grounded in organizational culture and people’s everyday practices. Practices that promote psychological safety, collective ownership and integration of risk-awareness were found to be critical. A key contribution of the study is the identification of local risk ambassadors, peer-level influencers who help translate strategic objectives into practical actions within projects. The research makes theoretical contributions by empirically validating prior PRM concepts, introducing new practice-based observations, and advancing understanding of PRMS implementation in multinational contexts. It also offers practical implications by showing how risk management can be more effectively embedded in complex and multicultural project environments. Finally, the findings suggest potential directions for future research, particularly on advancing culturally responsive and human-centred approaches to risk management in global construction industry.

Rakennusala on toimialana erittäin altis riskeille, sillä rakennushankkeet ovat tyypillisesti monimutkaisia kokonaisuuksia, joihin liittyy useita sidosryhmiä ja joita toteutetaan usein epävarmoissa sekä jatkuvasti muuttuvissa olosuhteissa. Tämän vuoksi tehokas projektiriskienhallinta on olennainen osa rakennusyritysten pitkäjänteistä menestystä. Riskienhallinnan systemaattinen toteuttaminen on kuitenkin edelleen haastavaa, erityisesti monikansallisissa organisaatioissa, joissa inhimilliset, kulttuuriset, ja kontekstuaaliset erot lisäävät monimutkaisuutta. Tutkimuksen tavoitteena oli lisätä ymmärrystä siitä, miten monikansalliset rakennusalan yritykset voivat vahvistaa projektiriskienhallinnan kyvykkyyksiään. Tätä tarkasteltiin kolmen alatutkimuskysymyksen kautta: ”Mitkä ovat tehokkaan projektiriskienhallintajärjestelmän keskeiset osa-alueet?”, ”Mitkä ovat keskeisimmät esteet projektiriskienhallintajärjestelmän tehokkaalle hyödyntämiselle monikansallisissa rakennusalan organisaatioissa?”, ja ”Mitkä kriittiset menestystekijät mahdollistavat projektiriskienhallintajärjestelmän tehokkaan toteuttamisen ja kehittämisen monikansallisissa rakennusalan organisaatioissa?”. Tutkimuksen tavoitteena oli tuottaa sekä akateemista ymmärrystä että käytännön suosituksia projektiriskienhallinta-järjestelmien kehittämiseksi. Tutkimus perustuu laadulliseen yhden tapauksen tapaustutkimukseen. Teoreettinen viitekehys pohjautuu kirjallisuuteen projektiriskienhallintajärjestelmistä ja niiden implementoinnin menestystekijöistä. Aineisto kerättiin puolistrukturoiduilla haastatteluilla, joissa haastateltiin asiantuntijoita kansainvälisestä rakennusyrityksestä. Tulokset osoittavat, että tehokas projektiriskienhallintajärjestelmän toteutus ei perustu pelkästään teknisiin rakenteisiin ja prosesseihin, vaan sen onnistumista määrittävät ennen kaikkea inhimilliset, kulttuuriset ja kontekstuaaliset tekijät, jotka ovat kerroksellisia ja keskinäisriippuvaisia. Keskeisiä havaintoja olivat muun muassa johtamisen rooli, luottamuksen rakentaminen, avoin viestintä ja jaettu vastuu riskienhallinnassa. Yksi tutkimuksen keskeisistä havainnoista oli niin sanottujen riskilähettiläiden rooli. Nämä epämuodolliset, vertaisjohtajuuteen perustuvat toimijat edistävät riskienhallintakäytäntöjen integroitumista osaksi päivittäistä projektityötä ja toimivat linkkinä strategisten tavoitteiden ja käytännön toteutuksen välillä. Tutkimus tuottaa teoreettisia kontribuutioita aiempien käsitteiden empiirisellä vahvistamisella ja käytäntölähtöisten havaintojen tuottamisella, erityisesti monikansallisen kontekstin näkökulmasta. Käytännön tasolla se tarjoaa suuntaviivoja siihen, miten riskienhallinta voidaan integroida tehokkaammin monimutkaisiin ja kulttuurisesti moninaisiin projektitoimintaympäristöihin. Lisäksi se avaa uusia tutkimuspolkuja kulttuurisensitiivisen ja ihmislähtöisen riskienhallinnan kehittämiseksi globaalilla rakennusalalla.
Keywords: Project risk management, risk management systems, critical success factors, implementation, construction industry, multinational organizations, qualitative research.